2010
DOI: 10.1364/oe.18.010323
|View full text |Cite
|
Sign up to set email alerts
|

Laser-self-mixing interferometry in the Gaussian beam approximation: experiments and theory

Abstract: We analyze the laser-self-mixing process in the Gaussian beam approximation and reformulate the expression of the feedback coefficient C in terms of the effective feedback power coupled back into the laser diode. Our model predicts a twenty-fold increase of the ratio between the maximum and the minimum measurable displacements judged against the current plane-wave model. By comparing the interaction of collimated or diverging Gaussian laser beams with a plane mirror target, we demonstrate that diverging beams … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…2. The measured LDR was limited by the experimental conditions but is comparable to the best ones reported with free space sources [5]. It is worth noting that the LSM signal preserved its shape in spite of using a non polarization maintaining fiber and even in presence of fiber solicitations during acquisition.…”
Section: Linear Dynamic Rangesupporting
confidence: 77%
See 1 more Smart Citation
“…2. The measured LDR was limited by the experimental conditions but is comparable to the best ones reported with free space sources [5]. It is worth noting that the LSM signal preserved its shape in spite of using a non polarization maintaining fiber and even in presence of fiber solicitations during acquisition.…”
Section: Linear Dynamic Rangesupporting
confidence: 77%
“…It can be in principle as long as the coherence length of the laser, whereas in practice it is limited by the loss of signal due to occasional off-axis vibrations of the sliding target causing optical misalignment of the collimated beam. We shown that, contrary to the usual habit of using collimated or focused beams, a small divergence of the laser beam significantly improves the signal stability extending the LDR to about 2 meters [5]. To achieve the required feedback power it is then possible either tuning the divergence losses in the external cavity or increasing the fiber losses by bending the fiber around a small mandrel.…”
Section: Linear Dynamic Rangementioning
confidence: 97%
“… ( a ) Variation of feedback coefficient C for a collimated (d = f) and a divergent (Δd = −0.3μm) Gaussian beam. ( b ) Maximum measurable tilt angle of a target at 1 m distance from the laser emitting a divergent Gaussian beam (adapted from Reference [ 35 ]). …”
Section: Figurementioning
confidence: 99%
“…Reflectance scanning confocal microscopy can be conveniently performed, at any wavelength, by optical feedback interferometry (OFI) [3]. OFI is a common path detectorless technique based on the laser self-mixing effect (LSM) [4]. In LSM, light emitted by the laser and back scattered by the sample, mix in the laser cavity providing a modulation signal conveniently acquired either by a photodetector, or by a voltage probe at the laser terminals [5], in the case of semiconductor lasers.…”
Section: Introductionmentioning
confidence: 99%